Personal Branding Selebritas dan Bisnis Online Shop - Rostika Yuliani; Susanne Dida (MediaTor (Jurnal Komunikasi), 2018)
Personal branding can simply be interpreted as a brand development on a person. Zaskia Adya Mecca is a successful actor and presenter still build her career to this day, and at the beginning of 2012 Zaskia Adya Mecca released Muslim clothing business that is sold both online and offline.  Her purposes to running the business is to make society interested to buy her products by utilizing the existing technology through the website, social media such as instagram. The motive of Zaskia Adya Mecca doing personal branding by using social media in instagram and website is to promote products owned by Zaskia Adya Mecca to the fans and consumers so they will interested to buy products that are sold both online and offline. The superiority of the products owned by Zaskia Adya Mecca are attractive models, simple, elegant, limited models and the price is still affordable by some circles, especially the upper middle class.